2011
DOI: 10.4028/www.scientific.net/msf.697-698.133
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Surface Quality on Dry Belt Grinding of Ti6Al4V Alloy

Abstract: This paper deals with an investigation of surface integrity of Ti6Al4V alloy with zirconia alumina and SiC belts. The experiments were conducted under dry grinding environments in milling machine XS5040 equipped with belt grinding device. Microcosmic geometry parameters were measured with TALYSURF5 instrument, the surface morphology machined workpiece and the phase structure was analyzed using 3D viewer microscope, surface hardness for ground surface was measured by HXS-1000A instrument. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In another study, dry grinding conditions in milling machine XS5040 attached with belt grinding equipment were performed [81]. Properties like surface integrity of the alloy with zirconia alumina and SiC belts were examined.…”
Section: Impact Of Type Of Abrasivementioning
confidence: 99%
“…In another study, dry grinding conditions in milling machine XS5040 attached with belt grinding equipment were performed [81]. Properties like surface integrity of the alloy with zirconia alumina and SiC belts were examined.…”
Section: Impact Of Type Of Abrasivementioning
confidence: 99%
“…Huo et al investigated the grinding of a Ti6Al4V alloy with a superabrasive grinding wheel and analyzed the effect of the process parameters on SR. The results showed that the SR decreased with the decrease of grinding depth and increased with the decrease of the grinding wheel speed [9]. Bigerelle et al established a wear mechanism model for abrasive belt grinding and polishing, and studied the influence of process parameters on the SR [10].…”
Section: Introductionmentioning
confidence: 99%